The discrepancies of wing hamuli numbers in Indo-Malayan stingless bees observed under scanning electron microscope (SEM) - Zubaidah, A.H.; Shamsul, B. (2016)
Wing hamuli in stingless bee are considered as one of the unique characteristics and could be used as the features in taxonomy and identification of species. The number of wing hamuli differs from species to species. Wing hamuli can be found on the hind wing, which link the fore wing of the stingless bee for a distant foraging. In this experiment, nine Indo-Malayan stingless bee species were collected from a specialized collection center in Sekayu, Terengganu, Malaysia (Indo- Malayan Meliponine Respository Sekayu) and stingless bee farm in Jalan Kebun, Selangor. Uncoated fresh samples were introduced into the low-vacuum chamber of the SEM and observed for their wing hamuli on both the right and left wing. Observation under the SEM shows clearer hamuli morphology as compared to stereomicroscopy. Result shows the number of wing hamuli on left and right wing of certain stingless bees are not similar. Samples of Geniotrigona thoracica exhibits variation wing hamuli. Some has 8 hamuli on the left wing and 9 on the right wing or 10 hamuli on left and 9 hamuli on the light or both wings have 8 hamuli. There are also variation in Homotrigona aliceae wing hamuli. Some has 7 or 8 hamuli on both wings or 8 hamuli on right and 7 on the left. On the other hand, Homotrigona fimbriata shows both with either 8 or 7 hamuli. Most of Tetrigona apicalis shows 7 hamuli on both wings except, one sample with 8 hamuli on the left and 7 on the right. Heterotrigona erythrogastra (7 hamuli), Heterotrigona itama (7 hamuli) Tetragonilla colllina (6 hamuli), Tetrigona melanoleuca (6 hamuli) and Tetrigona vidua (7) exhibit a similar number of hamuli 011 both wings.